The filter bubble : how the new personalized Web is changing what we read and how we think - Pariser, Eli. (New York, N.Y. : Penguin Books/Penguin Press, 2012)
A filter bubble is a term coined by internet activist Eli Pariser in his book by the same name to describe a phenomenon in which websites use algorithms to selectively guess what information a user would like to see, based on information about the user (such as location, past click behaviour and search history). As a result, websites tend to show only information which agrees with the user's past viewpoint, effectively isolating the user in a bubble that tends to exclude contrary information.
The race for relevance -- The user is the content -- The Adderall society -- The you loop -- The public is irrelevant -- Hello, world! -- What you want, whether you want it or not -- Escape from the city of ghettos.
Includes bibliographical references and index.
Keywords: Invisible Web; Information organization; Semantic Web -- Social aspects; World Wide Web -- Subject access; Internet -- Censorship